Bioavailability of microplastic-bound pollutants in vitro: The role of adsorbate lipophilicity and surfactants - Heinrich, Patrick; Braunbeck, Thomas (Comparative biochemistry and physiology. Part C, Toxicology & pharmacology, 2019)
The potential role of microplastic particles (MPs) as vectors for lipophilic organic pollutants enhancing their uptake by organisms has repeatedly been discussed in the scientific community. Likewise, several studies indicate an important role of surfactants in pollutant-transfer from MP to organisms. Employing polyethylene particles, the bioavailability of three MP-bound inducers of 7-ethoxyresorufin-O-deethylase (EROD) with variable lipophilicity was quantitatively compared via EROD activity in RTL-W1 cells. In addition, non-cytotoxic surfactant concentrations of Pluronic F-127, rhamnolipids, sodium deoxycholate and sodium dodecyl sulfate (SDS) supplemented to the medium were tested for their effects on pollutant desorption from MPs as well as on cellular EROD induction. Bioavailability of MP-bound pollutants was negatively correlated with lipophilicity, and all surfactants were found to modulate the cellular response towards inducers by unidentified mechanisms. After experimental correction for effects on the cellular response, all surfactants except SDS moderately increased desorption of inducer from MPs. Results on the impact of lipophilicity agree with previously published thermodynamic models, indicating that appreciable pollutant desorption from MPs may only occur for substances with comparatively low lipophilicity, the accumulation of which on MPs is negligible in the environment. However, the role of surfactants should be considered further with respect to potential effects on sorption of pollutants to and from MPs.
Gesehen am 17.06.2019